House dust mite‐specific immunotherapy with two licensed vaccines: Outcome under clinical routine conditions. Issue 2 (5th March 2017) - Mahler, Vera; Klein, Christian; Sager, Angelika; Zimmermann, Jürgen
Abstract: Introduction: House dust mite (HDM) allergens are major causes for the development of allergic diseases. A disease modifying effect and clinical benefit of allergen immunotherapy (AIT) has been demonstrated in a number of clinical trials. Clinical trials, however, are carried out in selected populations under specific conditions based on inclusion and exclusion criteria and may not represent the entire patient population from medical practice. Objective of this study conducted in patients with HDM allergy was to systematically collect information about the benefit of AIT under clinical routine conditions. Methods: In this prospective, multi‐center non‐interventional study, 220 patients (117 adults, 103 children) with HDM allergy receiving subcutaneous AIT with Depigoid ® were monitored for 2 years. Organ‐specific key symptoms, health‐related quality of life (QoL), and the use of concomitant anti‐allergic medication were assessed at baseline and after 12 and 24 months. Effectiveness and tolerability of the AIT was assessed by physicians and patients. Occurrence of adverse events (AEs) was continuously monitored. Results: Two hundred and nineteen patients (116 adults, 103 children) were evaluated. A major improvement of the total symptom‐score was observed after 24 (12) months in 76% (72%) and 80% (79%) of adults and children, respectively, accompanied by a reduction in concomitant anti‐allergic medication and a pronounced improvement in QoL. The effectiveness and tolerability of the AIT was estimated as very good/good by 80–90% of physicians and patients. AEs were observed in 4/117 adults (3.4%) and in 7/103 children (6.8%). Serious AEs were reported in three adults and one child: A grade‐II anaphylactic reaction (one adult) controlled by oral antihistamines (no hospitalization) classified as "definitely, " three others as not (2) or possibly (1) drug‐related. Conclusions: The data collected from 220 patients confirm the efficacy, tolerability/safety, and acceptance of AIT with Depigoid ® in adults and children with HDM allergy under routine clinical conditions. Abstract : A disease modifying effect and clinical benefit of allergen immunotherapy (AIT) has been demonstrated in a number of clinical trials. Clinical trials, however, are carried out in selected populations under specific conditions based on inclusion and exclusion criteria and may not represent the entire patient population from medical practice. Here we present data collected under routine clinical conditions from 220 patients which confirm the efficacy, tolerability/safety, and acceptance of AIT with a licensed allergy vaccine in adults and children with HDM allergy under routine clinical conditions.